Sistem Rekomendasi Perbaikan Jalan di Makassar Dengan Metode AHP-TOPSIS - Andi Amaliyah Maryama; Nurul Hidayat; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Road damage is one of the many problems experienced in Indonesia, especially in the capital city, such as Makassar as the capital of South Sulawesi Province and becoming focus of problems that must be resolved by the local government Unfortunately, there is no balance between the number of damage roads and the budget. So, the government needs a system to help the government in recommending road improvements based on factors that can be quantified. This thesis will discuss the application of AHP-TOPSIS method to determine road priority recommendations to be repaired. The AHP (Analytical Hierarchy Process) method in this case will play a role in the weighting process and continue with the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to calculate the shortest distance between the alternative with the value of the positive ideal solution. AHP method includes several processes, such as normalization, calculation of eigen vector values, calculation of index value consistency and calculation of the value of consistency ratio. While the TOPSIS method includes several processes namely normalization, calculation of positive and negative ideal matrices then proceed with the calculation of the maximal measure max value and separation measure min. This system uses data from 78 data which form the basis of calculations and 10 road recommendation data which become test data. The application of the AHP-TOPSIS method to determine priority recommendations for road repair in Makassar using various factors such as: good road conditions, moderate road conditions, damaged road conditions, severely damaged road conditions and LHR (average daily traffic). From this study obtained an accuracy value of 70% due to the difference between the results of system trials with data obtained from the Public Works Office of the City of Makassar.